2022
DOI: 10.1186/s12920-022-01207-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of m6A methylation and its impact on prognosis, genome instability, and tumor microenvironment in hepatocellular carcinoma

Abstract: Background N6-methyladenosine (m6A) RNA regulation was recently reported to be important in carcinogenesis and cancer development. However, the characteristics of m6A modification and its correlations with clinical features, genome instability, tumor microenvironments (TMEs), and immunotherapy responses in hepatocellular carcinoma (HCC) have not been fully explored. Methods We systematically analyzed the m6A regulator-based expression patterns of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…RNA m 6 A methylation has recently been shown to regulate tumor progression through effects on GI [ 255 ]. Yin et al [ 256 ] reported that multiple m 6 A regulators (METTL3, WTAP, YTHDF1/2/3) are associated with GI and mediate poor prognosis in HCC. Interestingly, METTL3-catalyzed m 6 A methylation is reported to mediate downregulation of the HMBOX1 gene, resulting in telomere dysfunction and inactivation of p53 signaling, thereby affecting telomere homeostasis and genome stability and promoting tumorigenesis [ 257 ].…”
Section: A Methylation Regulates the Biological Functions Of Tumor Cellsmentioning
confidence: 99%
“…RNA m 6 A methylation has recently been shown to regulate tumor progression through effects on GI [ 255 ]. Yin et al [ 256 ] reported that multiple m 6 A regulators (METTL3, WTAP, YTHDF1/2/3) are associated with GI and mediate poor prognosis in HCC. Interestingly, METTL3-catalyzed m 6 A methylation is reported to mediate downregulation of the HMBOX1 gene, resulting in telomere dysfunction and inactivation of p53 signaling, thereby affecting telomere homeostasis and genome stability and promoting tumorigenesis [ 257 ].…”
Section: A Methylation Regulates the Biological Functions Of Tumor Cellsmentioning
confidence: 99%
“…In addition, YTHDF3 contributed to hepatocarcinogenesis of mice induced by chemical carcinogens. At the same time, an analysis of the expression pattern of m 6 A regulator from Cancer Genome Atlas and Gene Expression Omnibus Database also shows that the expression of YTHDF3 is significantly increased in HCC tissues compared with normal tissues, and the high expression of YTHDF3 is closely related to the poor prognosis of HCC patients [ 13 ]. Moreover, highly-expressed lysine-specific demethylase 5B can promote proliferation, migration, invasion and other malignant phenotypes of HCC cells through miR-448 /YTHDF3/ITGA6 (Integrin subunit alpha 6) axis in hepatocellular carcinoma, confirming that YTHDF3 plays an important role in the occurrence and development of HCC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, research has shown that m6A modifiers are correlated with AML; for example, Huang et al found that fat mass and obesity-associated protein (FTO) is a mRNA m6A demethylase that can be targeted by small molecule inhibitors and has the potential to treat AML ( 12 ). Methyltransferase-like 14 ( METTL14 ) modulates its mRNA target through m6A modification to exert its carcinogenic effect, and METTL14 and m6A modification have key roles in normal and malignant hematopoiesis ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies have examined the relationship between the m6A-related signatures and TIME. There is also a study that enhances the understanding of the heterogeneity and complexity of TIME through a comprehensive analysis of specific m6A modulators to guide related immunotherapy ( 14 ). Unfortunately, these studies did not extend to AML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation